Reconceiving religious conflict
1 online resource (xiv, 258 pages)
Keywords: "This book deconstructs instances of religious conflict within the formative centuries of Christianity, the first six centuries CE. It explores the theoretical foundations of religious conflict; the dynamics of religious conflict within the context of persecution and martyrdom; the social and moral intersections that undergird the phenomenon of religious conflict; and the relationship between religious conflict and religious identity. It is unique in that it does not solely focus on religious violence, as it is physically manifested, but on religious conflict (and tolerance), looking too at dynamics of religious discourse and practice that often precede and accompany overt religious violence."--Provided by publisher.